Pembuatan Media Kompos Siap Pakai sebagai Solusi Sampah Organik Rumah Tangga - Reni Srimulyaningsih; Sri Wilujeng; Toni Supriyanto; Ishak Tan; Prasetyo Widodo (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Household organic waste is one of the environmental issues that requires sustainable management to reduce the amount of waste disposed of in landfills. This community service activity aimed to improve community knowledge and skills in managing household organic waste through the production of ready-to-use compost media. The activity was conducted on May 11, 2026, at Mushola Cluster D'Venue, RT 02 RW 20, Cileunyi Kulon Village, Cileunyi District, Bandung Regency, involving 20 members of a women's Islamic study group (Majlis Ta'lim). The methods employed included counseling, discussions, demonstrations, hands-on practice, and evaluation through pre-tests and post-tests. The results showed an improvement in participants' knowledge across all measured indicators. The average knowledge score increased from 38.02% in the pre-test to 78.64% in the post-test, representing an increase of 40.62%. The highest improvement was observed in the indicator of ready-to-use compost media knowledge, which increased by 51.56%. In addition to enhancing knowledge, the activity also improved participants' practical skills in producing ready-to-use compost media independently. These findings indicate that the combination of counseling and hands-on practice is effective in strengthening community capacity for household organic waste management and promoting the utilization of compost as a valuable planting medium.